Pnevmokonioze - Jerše, Maja (Medicinski razgledi, 2012)
Pneumoconioses are still a common cause of chronic lung disease. The term pneumoconiosis- refers to reactions ofthe lun gs to inhaled mineral or organic dusts, and resultant alteration in their structure. The pathologic findings can resemble those of other fibrotic and granulom ato us disorders in the lung. The knowledge acquired through research has be en most valuable in determining the cause and pathogenesis of these occupational diseases. The toxicity, and hence fibrogenicity, of particulates is related to both the nature of the dust and the nature of the host response. Many of the dusts have a characteristic reaction pattern or appearance in histologic sections, which permits an accurate diagnosis. Others are associated with areaction pattern that may suggest thediagnosis, but a careful occupational history and supplemental analytical techniques may be required to confirm the diagnosis. In industrialized countries, improvements in working conditions and dust controls measures have led to a decrease in the incidence of severe diseases of some classic- forms of pneumoconioses, such as silicosis, coal workers' pneumoconiosis, asbestosis. In recent years, a great progress in understanding, clinical characteristics, epidemiology and basic pathogenesis has been made in the field of metal-related parenchymal disorders. Although the particular substance or metal are the major contributory factors in the pathogenesis, not all individuals exposed to similar levels develop disease, thus suggests that there is a genetie predisposition to the development of pneumoconiosis. Therefore, it is crucial to identify the high-risk individuals to prevent the progress of the disease.
Keywords: lung; pljuča; pneumoconiosis; pnevmokonioza; poklicna obolenja; disease, occupational; dust; prašni delci